STABILITY ANALYSIS OF STATIC SLIP-ENERGY RECOVERY DRIVE VIA EIGENVALUE METHOD (Nigerian Journal of Technology, 2008)
The stability of the sub synchronous static slip energy recovery scheme for the speed control of slip-ring induction motor is presented. A set of nonlinear differential equations which describe the system dynamics are derived and linearized about an operating point using perturbation technique. The Eigenvalue analysis of the linearized model shows that the drive system is almost completely stable in the entire operating range Routh stability criterion is used in the polar plots of roots of the characteristics equations of induction machine drive on the ?-j? plane which further justified the above results.